Effect of coagulants on the chemical and microbial quality of fresh cheese (Bangladesh Journal of Animal Science, 2022)
This experiment was conducted to explore the effect of various types of coagulants on the chemical and microbiological quality of cheese made from fresh milk. Fresh cheese was manufactured using four different coagulants; microbial rennet (0.7%), lactic acid (1.5%), papaya latex (5 drops in 100 mL water) and calf rennet (100 g calf abomasum soaked overnight in 1000 mL mixture of water and milk in 3:1 ratio and then filtrate) under laboratory condition and analyzed for cheese yield, proximate composition, acidity, pH and coagulation time. In addition, standard plate count and coliform count was also performed. Result revealed that using microbial rennet as coagulant gave  the maximum yield of cheese (225 g/Kg milk) followed by calf rennet and lactic acid, and papaya latex had the minimum value (215g/Kg milk) in this regard (p=0.013). Microbial rennet took the lowest time (22 min) to coagulate the milk which was 14-34 min less than that of the other coagulants, and lactic acid had the slowest (54 min) coagulating action in cheese manufacturing process (p=0.000). In addition, cheese that are manufactured by microbial rennet and calf rennet were superior in terms of chemical composition compared to the cheese in which lactic acid and papaya latex was used as coagulant (p=0.000-0.047). But the calcium concentration was found maximum in papaya latex cheese. Acidity was found highest in lactic acid cheese and papaya latex cheese had the highest pH value. On the other hand, standard plate count and coliform count was found highest in cheese coagulated by lactic acid, where microbial rennet cheese had the lowest count,  and the microbial count of other two cheese was intermediate of them (p=0.000-0.001). Overall, microbial rennet, lactic acid, papaya latex, and abomasum rennet could be used to make cheese successfully, however, with a preference to microbial rennet.Bang. J. Anim. Sci. 2021. 50 (2): 73-79